Tác động của phân cấp tài khoá đến thu hút dòng vốn đầu tư trực tiếp nước ngoài vào Việt Nam - Diep Gia , Luat; Bui Duy , Tung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This paper investigates the impact of fiscal decentralization on attracting FDI flows to Vietnam. Using panel data of provinces over the 2002–2014 period, we detect the fiscal decentralization with its positive and significant effect on FDI inflows. After controlling for other variables, we find that using LSDV and GMM estimators helps overcome the problem of endogeneity of the variables in the model. Based on the testing results, several policy implications are proposed for further adjustment to the procedure of fiscal decentralization and for more effective FDI attraction in the future.
Keywords: Fiscal decentralization; FDI; panel data; LSDV; GMM